Directed Fusion of Mesenchymal Stem Cells with Cardiomyocytes via VSV-G Facilitates Stem Cell Programming. (30th May 2012) - Kouris, Nicholas A.; Schaefer, Jeremy A.; Hatta, Masato; Freeman, Brian T.; Kamp, Timothy J.; Kawaoka, Yoshihiro; Ogle, Brenda M.
Abstract : Mesenchymal stem cells (MSCs) spontaneously fuse with somatic cells in vivo, albeit rarely, and the fusion products are capable of tissue-specific function (mature trait) or proliferation (immature trait), depending on the microenvironment. That stem cells can be programmed, or somatic cells reprogrammed, in this fashion suggests that stem cell fusion holds promise as a therapeutic approach for the repair of damaged tissues, especially tissues not readily capable of functional regeneration, such as the myocardium. In an attempt to increase the frequency of stem cell fusion and, in so doing, increase the potential for cardiac tissue repair, we expressed the fusogen of the vesicular stomatitis virus (VSV-G) in human MSCs. We found VSV-G expressing MSCs (vMSCs) fused with cardiomyocytes (CMs) and these fusion products adopted a CM-like phenotype and morphology in vitro . In vivo, vMSCs delivered to damaged mouse myocardium via a collagen patch were able to home to the myocardium and fuse to cells within the infarct and peri-infarct region of the myocardium. This study provides a basis for the investigation of the biological impact of fusion of stem cells with CMs in vivo and illustrates how viral fusion proteins might better enable such studies.